Engineering Microstructure with Evaporation‐Induced Self‐Assembly of Microdroplets. Issue 6 (2nd May 2018) - Zhu, Pingan; Kong, Tiantian; Zhou, Chunmei; Lei, Leyan; Wang, Liqiu
Abstract: Natural systems have exceptional capabilities of constructing structures across multiple length scales for remarkable performances from limited choices of building blocks. However, simultaneous control over structures at both the macroscopic and microscopic length scales is restricted by the high requirements in the type and property of building blocks. Here, directed self‐assembly of microdroplets in an evaporating liquid is harnessed to fabricate large‐scale ordered films with precisely controlled microstructures. Evaporation‐induced variations in liquid confinement allow microdroplets to reassemble for large‐scale ordered patterns. Deformation of microdroplets into different shapes accurately defines multiple topographical structures at the microdroplet level. The fabrication process is facile and scalable, and works with various materials for manufacturing functional films with tunable properties. These results suggest a facile yet effective strategy for engineering microstructures by combining directed self‐assembly with manipulation of the property of building components for both structural fidelity and diversity. Abstract : A combination of evaporation‐induced self‐assembly and deformation of microdroplets is proposed to control microstructures with large‐scale ordering and microscale structural diversity. Using liquid droplets as building blocks, the method is able to fabricate a variety of precisely controlled microstructures with tunable properties.